2021
DOI: 10.1212/wnl.0000000000012512
|View full text |Cite
|
Sign up to set email alerts
|

Impact of C-Reactive Protein on Cognition and Alzheimer Disease Biomarkers in Homozygous APOE ɛ4 Carriers

Abstract: OBJECTIVE:Previous research has shown that elevated blood C-reactive protein (CRP) is associated with increased Alzheimer’s disease (AD) risk only in apoliprotein E4 genotype (APOE ε4) allele carriers. The objective of this study was to examine the interactive effects of plasma CRP and apoliprotein E (APOE) genotype on cognition and AD biomarkers.METHODS:Data from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) study was analyzed, including APOE genotype; plasma CRP concentrations; diagnostic status (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 30 publications
5
30
1
1
Order By: Relevance
“…This study extends our previous research 3, 4 by investigating if and how proinflammatory isoform of CRP, for example, mCRP, 6 , 7 , 8 can contribute to the cellular pathology of AD. Results showed that mCRP induced Aβ42 secretion and phosphorylated tau (p‐tau) production in primary neurons in a dose‐, time‐, and APOE genotype ( APOE ε4 > APOE ε3 > APOE ε2)‐dependent pattern.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This study extends our previous research 3, 4 by investigating if and how proinflammatory isoform of CRP, for example, mCRP, 6 , 7 , 8 can contribute to the cellular pathology of AD. Results showed that mCRP induced Aβ42 secretion and phosphorylated tau (p‐tau) production in primary neurons in a dose‐, time‐, and APOE genotype ( APOE ε4 > APOE ε3 > APOE ε2)‐dependent pattern.…”
Section: Discussionsupporting
confidence: 78%
“…These cellular pathologies are consistent and parallel with the interactive effects of APOE ε4 and CRP for AD risk 3 and AD brain biomarkers in humans. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C-reactive protein (CRP) is an acute-phase protein, the level of which rises during inflammation; however, evidence for its use as an AD biomarker remains inconclusive. Indeed, while some studies indicate that blood CRP levels correlate with Mini-Mental State Examination (MMSE) score, other results suggest that this is valid only among APOEε4 homozygote AD patients [ 88 , 89 ]. Still, no association with cognitive decline has been reported from independent data, leaving CRP as a debatable biomarker [ 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another group of genes (MAP2, METAP2, NFE2L2, SELP, SST, and VEGFA) was down-regulated by hypoglycemia and also downregulated in AD. A number of analyzed genes were suggested as potential targets for AD treatment, including ADIPOQ [83], AQP4 [84], CCL2 [85], CRP [86], EIF2AK3 [87], EPO [88], IGF1 [89], IGF1R [90,91], IGF2 [92,93], IGFBP2 [94], IL6 [95], NFE2L2 [96,97], NOS1 [98], NPY [99,100], PARK7 [101], SERPINE1 [102], SIRT1 [103], SIRT6 [81,104], SLC2A1 [105,106], TNF [107,108], VEGF and VEGFR [109]. The role of these molecules in hypoglycemia-induced brain dysfunction needs further research.…”
Section: Comparative Analysis Of the Gene Network Of Hypoglycemia Cognitive Decline And Admentioning
confidence: 99%